Pathogenesis and Treatment of Acne and Rosacea - Zouboulis, Christos C.; Zouboulis, Christos C.; Katsambas, Andreas D.; Katsambas, Andreas D.; Kligman, Albert M.; Kligman, Albert M. (Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book, written by experts from across the world, provides comprehensive coverage of acne and rosacea, focusing in particular on pathogenesis and treatment but also considering clinical aspects, prognostic factors, and impacts on quality of life. Both standard knowledge and important, clinically relevant insights that have emerged over the past decade are presented with the goal of assisting the reader in understanding these diseases and improving treatment outcome. It is explained how high-level research has recently given rise to a variety of new concepts in etiology and treatment, and emerging trends are also discussed. The book is in a reader-friendly format that highlights core messages with a very practical and clinical focus. Pathogenesis and Treatment of Acne and Rosacea will be an indispensable reference for all physicians who care for patients with acne or rosacea and for scientists working in the field.  .